Ía Mulher! - Uma análise antropo-semiótica da performance de Maria Padilha na umbanda - Cavalcante, Elita Maria Mendonça (2018)
Dissertation is about umbanda specifying in the entity exu Maria Padilha and its incorporation in Mãe Iara - a 61 years old woman, born in Fortaleza and a member of the Centro de Umbanda Rei Dragão do Mar. It is structured in three chapters: in the first, the objective is to perceive the context which umbanda was formed as a religion from the semiotic of culture perspective, considering the changes that went from its formation to the present; to clarify the particular characteristics that surround the figure of the exu into and out of the umbanda and its position of frontier in the religious universe; to understand how the incorporation develops in the ritual of exu from the perspective of the performance worked by authors like Goffman (1975), Turner (1988), Oliveira Jr (2011), Schechner (2006 e 2012) e Zumthor (2007), and how this body in trance becomes a media through the notion of "mediation processes" developed by Harry Pross and studied by Baitello (2011); and understand how this performance is generated and associated directly with the space in which it is inserted - the terreiro. In the second chapter we intend to deepen the study on the legends about Maria Padilha related by Meyer (1993); understand the insertion of Maria Padilha as an entity of umbanda; to perceive how the connection of this with Mãe Iara occurs; and capture the construction of the personification of Maria Padilha in the mother-of-santo, as are her clothes, the colors and the props chosen. In the third and final chapter the association between the previously worked concepts and the field records is made. The research is done through the use of the ethnographic method, having as data collection techniques the bibliographic research, semi-structured interview and participant observation. Oral testimonies of the mother-of-santo, photographs and videos of the ritual were collected in the years 2017 and 2018. This study focuses on the observation of the body in the act of trance, the performance built in this relation between mythical conceptions and physical communication. In this way, empirical research made it possible to understand how to construct the world understanding, the explanations and conflicts that mark the religious development of Mãe Iara and her affirmation as religious adept built and reinvented in everyday practices.